The Mighty Odds - Ignatow, Amy (Amulet Books, 2017)
When artsy cartoonist Martina, sweet nerd Nick, social outcast Farshad, and popular beauty queen Cookie are all in the same mysterious bus accident, they all develop very strange, seemingly insignificant "superpowers." Martina can change her eye color, while Nick can teleport just four inches to his left. Farshad has super strength only in his thumbs, and Cookie can read minds, so long as those minds are thinking about directions. An odd mix they make, but together they are oddly mighty. Now they must combine their powers to find out just what happened during the bus accident and why.